Presence of multiple genotypes in subjects with HPV-16 infection is highly associated with anal squamous intraepithelial lesions in HIV-1 infected males - Rovelli, Cristina; Poli, Andrea; Galli, Laura; Cernuschi, Massimo; Tamburini, Andrea Marco; Racca, Sara; Tambussi, Giuseppe; Rolla, Serena; Albarello, Luca; Rosati, Riccardo; Lazzarin, Adriano; Castagna, Antonella; et al. (PloS one, 2017)
The aim of the study was to determine the prevalence of abnormal cytological findings, high risk (HR)-HPV genotypes and to identify factors associated with an abnormal cytological findings in a cohort of HIV-infected males. Retrospective observational study on HIV-infected male patients who performed screening in the absence of clinical symptoms. Cytological abnormalities were classified as atypical squamous cells of undetermined significance (ASC-US), low-grade(LSIL) or high high-grade squamous intraepithelial lesion (HSIL). Logistic regression models were used to identify predictors of having LSIL/HSIL. Among 875 pts, abnormal cytology findings were observed in 254 (29%, 95% CI: 26.1%-32.1%) subjects: 142 (16%) had LSIL and 49 (6%) HSIL. Overall, 581 (66%, 95%CI: 63.2%-69.5%) subjects had ≥1 HR-HPV type and 269 (31%) had ≥2 HR HPV types. Multivariate logistic regression showed that subjects with multiple HR-HPV genotypes (OR = 1.351, 95%CI: 1.005-2.111) and with HPV-16 type (OR = 2.032, 95%CI: 1.313-3.146) were more likely to have LSIL/HSIL in addition to a lower CD4+/CD8+ ratio, a previous diagnosis of syphilis and a positive viral load. In another multivariate model, the presence of multiple HPV types in subjects with HPV-16 type was associated with the highest adjusted OR of having a LSIL/HSIL (OR = 2.598, 95%CI: 1.460-4.624). In HIV-infected men, the prevalence of abnormal cytological findings was of 29% and of HR-HPV was 66%. The concomitant presence of HPV-16 and multiple HR genotypes was associated with an increased risk of abnormal cytological findings. These data highlight the importance of screening multiple HPV genotypes in HIV-infected patients.